nargis TECHNIQUES OF MOTIVATING STUDENTS TO WRITE IN ENGLISH: TECHNIQUES OF MOTIVATING STUDENTS TO WRITE IN ENGLISH - Xushiyeva, Nargis (Журнал иностранных языков и лингвистики, 2022)
One of the biggest challenges teachers have faced in the classroom has to do with writing. Usually students do not want to write, because they have never been encouraged to do it or to enjoy it.